"Imitative" click chemistry to form a sticking xerogel for the portable therapy of bacteria-infected wounds. (18th October 2019) - Huang, Bo; Liu, Xiangmei; Tan, Lei; Cui, Zhenduo; Yang, Xianjin; Jing, Doudou; Zheng, Dong; Li, Zhaoyang; Liang, Yanqin; Zhu, Shengli; Yeung, Kelvin Wai Kwok; Wang, Xianbao; et al.
Abstract : Xerogels usually possess a stable structure and have a low swelling rate due to their inferior dynamics. Abstract : Xerogels usually possess a stable structure and have a low swelling rate due to their inferior dynamics. Herein, a xerogel was synthesized by "imitative" click chemistry based on lipoic acid for picking up bacteria from wound sites, and thus accelerating tissue repair. The cross-linking structure of disulfide and thioether inside the xerogel not only exhibited good ductility and intrinsic self-healing performance, but also showed superior biocompatibility. The xerogel captured more than 60% of the bacteria Staphylococcus aureus via strong electrostatic adsorption in the colonies with a bacteria count of 10 6 . In addition, this xerogel can stick to the skin in the form of patches in the wounds during therapy for wound healing and can be easily stripped from the skin after treatment, which makes it appropriate for the portable therapy of bacteria-infected wounds in emergency circumstances.